The Relationship between Boundary Work Tactics and Work-Family Conflict among Working Women - Nur Fatihah, A.B; Tay, Mila; Dayang Kartini, Abang Ibrahim; Zaiton, Hassan (UNIMAS Publisher, 2016)
This study aims to identify the relationship between boundary work tactics (behav-ioral, temporal, physical and communicative) and work-family conflict among work-ing women. A survey methodology was used in this study. This research involves the utilisation of questionnaire which was administered among one-hundred and three (103) working women currently working in a selected organisation. This study was conducted in a selected private organisation in Kuching, Sarawak. The relationship between boundary work tactics and work-family conflicts was analyzed using the Pearson’s correlation analysis test. The results of this study revealed that there is a significant relationship between behavioral tactics, temporal tactics, and communica-tive tactics with work-family conflict. Hence, from this study, the organisation can implement more strategic tactics to reduce work-family conflicts when the working women are challenged to balance responsibilities between their work and family.